2018
DOI: 10.1051/matecconf/201822601002
|View full text |Cite
|
Sign up to set email alerts
|

Ways to reduce the error of additive methods of forming

Abstract: The article is devoted to the investigation of the surface layer formation accuracy of engineering products by additive methods. The analysis of advantages and disadvantages of layered products synthesis technologies was carried out. It was revealed that, in additive shaping, the exact characteristics of the surface layer differ significantly from the accuracy characteristics of the surface layer of products obtained by the traditional methods. The analysis of domestic and foreign works on the topic of researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 7 publications
0
2
0
2
Order By: Relevance
“…Research carried out by research teams [11][12][13][14][15] shows that the formation of the internal structure of products with curvilinear layers makes it possible to obtain structures with higher strength characteristics compared to filling with flat layers. The development of models, algorithms and software is an urgent task.…”
Section: Relevance Of the Research Topicmentioning
confidence: 99%
“…Research carried out by research teams [11][12][13][14][15] shows that the formation of the internal structure of products with curvilinear layers makes it possible to obtain structures with higher strength characteristics compared to filling with flat layers. The development of models, algorithms and software is an urgent task.…”
Section: Relevance Of the Research Topicmentioning
confidence: 99%
“…В работах [2,3,4,5,6,7] был рассмотрен способ снижения погрешности формообразования, заключающийся в придании изделию в процессе выращи-вания ориентации, обеспечивающей аппроксимацию профиля изделия слоями поперечного сечения с меньшей кривизной.…”
Section: материалы и методы решения задачиunclassified
“…The questions [13] of the formation of errors during machining were investigated in the work. In it, the processing error was considered as a result of the action of the corresponding components: It should be noted that the shaping of parts by the method of welding with an electric arc in a protective gas, like most methods of additive shaping, is characterized by high values of the static component of the processing error, which, in general form, can be represented in the form of the equation [14,15]: There were published works [9][10][11][12], in which, as a result of theoretical studies, it was indicated that one of the measures to reduce the error in the shape of additive methods of shaping can be a change in the spatial orientation of the deposited layers. However, they do not represent information from experimental studies that confirm or refute the results obtained.…”
Section: Introductionmentioning
confidence: 99%